Vestibular-evoked myogenic potentials in miniature pigs - Xi Shi; Yan Zhang; Ya Li; Shiwei Qiu; Shili Zhang; Yaohan Li; Na Yuan; Yuehua Qiao; Shiming Yang (Journal of Otology, 2016)
Objective: To report detection of vestibular-evoked myogenic potentials (VEMPs) in the miniature pig. Methods: Potentials evoked by 1000 Hz tone bursts were recorded from neck extensor muscles and the masseter muscles in normal adult Bama miniature pigs anesthetized with 3% pentobarbital sodium and Carbachol II. Results: The latency of the first positive wave P from neck extensor muscles was 7.65 ± 0.64 ms, with an amplitude of 1.66 ± 0.34 uv and a rate of successful induction of 75% at 80 dB SPL. The latency of potentials evoked from the masseter muscles was 7.60 ± 0.78 ms, with an amplitude of 1.31 ± 0.28 uv and a rate successful induction of 66% at 80 dB SPL. Conclusion: The latencies and thresholds of VEMPs recorded from the neck extensor muscle and the masseter muscle appear to be comparable in normal adult Bama miniature pigs, although the amplitude recorded from the neck extensor muscle seems to be higher than that from the masseter muscle. However, because of their usually relatively superficial and easily accessible location, as well as their large volume and strong contractions, masseter muscles may be better target muscles for recording myogenic potentials.